Para Rollerski: sistematização de um programa de ensino para crianças e jovens com deficiência física - Pereira, Taylor Brian Lavinscky (2024)
Para Rollerski is an adapted discipline derived from Para Ski Cross Country (PSCC), a Paralympic winter sport practiced by individuals with physical and visual disabilities. Athletes use skis propelled by poles and compete in three categories: visually impaired, Standing, and sitting, the latter for participants who compete seated. In Brazil, the sport has developed thanks to rollerskiing, equipment that allows simulating PSCC techniques on asphalt. Rollerskiing has facilitated a growing number of participants in the country, enabling initial training on asphalt before transitioning to snow. This study aims to plan, implement, and evaluate a Para Rollerski teaching program for children and youth with physical disabilities. Specifically, it seeks to analyze the influence of the Para Rollerski teaching program on the individual development of participants in the sport's fundamentals before and after the proposed intervention. Additionally, it evaluates the suitability of the Para Rollerski teaching program for beginners with physical disabilities in this sport. This qualitative and quantitative study is characterized as a field research with a quantitative-descriptive approach focused on program evaluation. The study sample consisted of two physically disabled participants aged between 10 and 14 years. Data collection instruments included interviews using the PEI-EF, systematic observation via a field diary, the Para Rollerski Initiation Assessment Protocol (PAI-PR), and a protocol for evaluating sports initiation programs, both developed by the researcher to assess program effectiveness and participant progress. The PAI-PR was administered before and after a six-month intervention period, comprising 24 weekly sessions. Following program completion, a program evaluation protocol was administered by six judge-researchers specializing in Adapted Physical Activity. Descriptive statistics were used to analyze the results. Findings indicated that the sports initiation program was effective in achieving its objectives and had positive effects on learning basic skills in the sport among children and youth with physical disabilities, particularly those in the sitting category. The program employed strategies that promoted learning, development, and participant engagement. In conclusion, an initiation program for Para Rollerski with a pedagogical approach emphasizing playfulness and enjoyment in execution, while deemphasizing performance, proved beneficial for learning new skills and fundamentals, preventing dropout, and ensuring participant retention.